Influence of calcineurin inhibitor choice on outcomes in kidney transplant recipients aged ≥60 Y: a collaborative transplant study report - Echterdiek, Fabian Friedrich; Döhler, Bernd; Latus, Joerg; Schwenger, Vedat; Süsal, Caner (Transplantation, 2022)
Export - - Background. - Patients aged ≥60 y represent the fastest growing population among kidney transplant recipients and waitlist patients. They show an elevated infection risk and are frequently transplanted with multiple human leukocyte antigen mismatches. Whether the choice of calcineurin inhibitor influences graft survival, mortality, or key secondary outcomes such as infections in this vulnerable recipient population is unknown. - Methods. - A total of 31 177 kidney transplants from deceased donors performed between 2000 and 2019 at European centers and reported to the Collaborative Transplant Study were analyzed using multivariable Cox and logistic regression analyses. All recipients were ≥60 y old and received tacrolimus (Tac) or cyclosporine A on an intention-to-treat basis, combined with mycophenolic acid or azathioprine plus/minus steroids. - Results. - The risk of 3-y death-censored graft loss and patient mortality did not differ significantly between Tac- and cyclosporine A-treated patients (hazard ratio 0.98 and 0.95, P = 0.74 and 0.20, respectively). No difference was found in the overall risk of hospitalization for infection (hazard ratio = 0.95, P = 0.19); however, a lower incidence of rejection treatment (hazard ratio = 0.81, P < 0.001) was observed in Tac-treated patients. Assessment of pathogen-specific hospitalizations revealed no difference in the risk of hospitalization due to bacterial infection (odds ratio = 1.00, P = 0.96), but a significantly higher risk of hospitalization due to human polyomavirus infection was found among Tac-treated patients (odds ratio = 2.45, P = 0.002). The incidence of de novo diabetes was higher for Tac-based immunosuppression (odds ratio = 1.79, P < 0.001). - Conclusions. - Calcineurin inhibitor selection has no significant influence on death-censored graft survival, mortality, and overall infection risk in ≥60-y-old kidney transplant recipients.